Indonesian Hajj diplomacy to increase Hajj quota during 2015-2023 - Hasbiyani Kamilah Istahar; Kirana Putri Aulia; Windy Dermawan; Akim Akim (Goodwood Publishing, 2023)
Purpose: The purpose of this study is to determine the forms of Hajj diplomacy carried out by the Indonesian government to overcome the long waiting period for Hajj pilgrims. Research methodology: This study used a qualitative research method that utilizes secondary data as the data source. The secondary data mostly refer to various publications, such as books, journals, news, archives, social media, the official website of the Indonesian Ministry of Religious Affairs, and other sources that are factual and relevant to the topic. Results: The Indonesian government uses two tracks of diplomacy in Hajj affairs. The first track of diplomacy is bilateral relations with the Saudi Arabian government, either through meetings between the heads of the state or meetings with other relevant stakeholders. Meanwhile, the second track diplomacy is through the relationship between Indonesian non-governmental actors such as Indonesian Hajj and Umrah travel entrepreneurs with the Saudi Arabian authorities to obtain non-governmental Hajj quotas or commonly referred to as Hajj Furoda from the Saudi Arabian government. Conclusion: These two forms of diplomacy reflect Indonesia’s adaptive strategy in managing Hajj demand amid quota limitations, balancing state and non-state cooperation. Limitations: This study focused only on the years 2015–2023. It also relies on secondary data that may not provide a comprehensive understanding of the dynamics and processes underlying Indonesia's Hajj diplomacy. Furthermore, this study only explores one non-state actor involved in Hajj diplomacy, namely, Hajj and Umrah travel entrepreneurs. Contributions: This study provides valuable insights and recommendations to policymakers, researchers, and stakeholders regarding the dynamics of Indonesia's Hajj diplomacy and its impact on international relations.